The implementation of the guiding principles on business and human rights. Implications for States - Lucena Cid, Isabel Victoria (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
In this paper we focused on one of the main aspects contained in the document UN Guiding Principles on Business and Human Rights related to the responsibility of States for its implementation. First, we have selected the guiding and operational principles aimed to States to assume a political commitment to promote effective protection of human rights by businesses. Secondly, we analyzed the actions undertaken by the Spanish State in compliance with the commitments made within the EU and UN, and finally, we conclude with some proposals on the National Action Plan on Business and Human Rights.doi: https://doi.org/10.20318/universitas.2017.3557
Keywords: Human Rights; business; State; guiding principles; National Action Plan